2015
DOI: 10.1007/s11274-015-1842-1
|View full text |Cite
|
Sign up to set email alerts
|

Sediment prokaryote communities in different sites of eutrophic Lake Taihu and their interactions with environmental factors

Abstract: To investigate the temporal variation of the sediment prokaryote communities and their relation with the rapid increase of algae population in Taihu, a shallow eutrophic freshwater Lake, water and surface sediments were sampled from seven sites in different stages of algal bloom. The physicochemical characterization revealed positive correlations among the nutrient (N, P) parameters in the water and sediments, as well as TN/TP ratio 30.79 in average in water and 0.13 in sediments, demonstrating that P content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 72 publications
6
29
1
1
Order By: Relevance
“…As shown by the cluster analysis, the sediment samples (except for GS2‐2) distributed in Figure a are closely grouped compared to the samples distributed in Figure b. This grouping means that the microbial community structure of alpine lake sediments in different locations also has spatial heterogeneity, which is consistent with previous reports (Bai et al., ; Chen et al., ; Dai et al., ; Song, Li, Du, Wang, & Dinget al, ). This spatial heterogeneity may be related to scale; spatial distance plays an important role in the formation of microbial community composition differences in the range of 10–1,000 km (Martiny, Eisen, Penn, Allison, & Horner‐Devine, ; Martiny et al., ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As shown by the cluster analysis, the sediment samples (except for GS2‐2) distributed in Figure a are closely grouped compared to the samples distributed in Figure b. This grouping means that the microbial community structure of alpine lake sediments in different locations also has spatial heterogeneity, which is consistent with previous reports (Bai et al., ; Chen et al., ; Dai et al., ; Song, Li, Du, Wang, & Dinget al, ). This spatial heterogeneity may be related to scale; spatial distance plays an important role in the formation of microbial community composition differences in the range of 10–1,000 km (Martiny, Eisen, Penn, Allison, & Horner‐Devine, ; Martiny et al., ).…”
Section: Resultssupporting
confidence: 88%
“…As shown by the cluster analysis, the sediment samples (except for GS2-2) distributed in Figure 1a are closely grouped compared to the samples distributed in Figure 1b. This grouping means that the microbial community structure of alpine lake sediments in different locations also has spatial heterogeneity, which is consistent with previous reports (Bai et al, 2012;Chen et al, 2015;Dai et al, 2015;Song, Li, Du, Wang, & Dinget al, 2015). This spatial heteroge-…”
Section: Comparison Of Microbial Community Structure Among Sedimentsupporting
confidence: 92%
“…This result is very similar to the recent pyrosequencing analysis of Lake Taihu which identified Proteobacteria, Actinobacteria, and Bacteroidetes as the dominant groups (21). Also, the composition of the sediment samples was consistent with the previous investigation (22). The main genera in the sediments are clearly different from those found in the water column, which documents that our samples are representative for the selected environments and that they are free of any potential cross-contamination.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies indicated that Epsilonproteobacteria was abundant in the animals' digestive tracts and near undersea hydrothermal vents, and that it exhibited good resistance to toxicity [59,60] and the ability to degrade some toxic substances [61]. However, Epsilonproteobacteria has rarely been detected in the sediments in the Taihu Basin [62]. Previous studies indicated that Deltaproteobacteria was ubiquitous in the environment, and closely related to the sulfur cycle between the water and sediment [63].…”
Section: Discussionmentioning
confidence: 99%